Postnatal human lung growth. - Thurlbeck, W M (1982)
Standard morphometric methods were applied to the lungs of 36 boys and 20 girls aged from 6 weeks to 14 years, dying as a result of trauma or after short illnesses. Individual lung units, alveolar dimensions, and number of alveoli per unit area and volume did not differ between boys and girls, but boys had bigger lungs than girls for the same stature. This resulted in a larger total number of alveoli and a larger aveolar surface area in boys than in girls for a given age and stature. There may be more respiratory bronchioles in boys than girls. There was rapid alveolar multiplication during the first two years of life and alveolar dimensions and number of alveoli per unit area and volume did not change much during this period. There was little or no increase in the total number of alveoli after the age of 2 years but the data are hard to interpret. There is a wide scatter of the total number of alveoli in the growing lung, in keeping with the observation that the total number of alveoli is very variable in adults. Prediction data are given for the various morphometric variables studied.